Pengembangan Kurikulum Berbasis Nilai-Nilai Islam dalam Manajemen Lembaga Pendidikan Islam di MTS Al-Wardah Tembung - Afik Faeyza; Evy Juliani; Maisa Muti Salsabilla; Salwa Putri Ferhan; Amiruddin Siahaan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Basically the purpose of a curriculum development based on Islamic values in the management of Islamic educational institutions, yes, it is something that aims to know how the development of an Islamic value in curriculum development and also to know the level of knowing for students will have the potential in knowing Islamic values. Thus, in developing a curriculum based on Islamic values in the management of educational institutions, it is also the main thing to ensure that students get a good education and help them reach their full potential accompanied by Islamic values. Thus from the statement that has been conveyed that the purpose of this research includes to further study how a curriculum development based on Islamic values in the management of Islamic educational institutions in an educational institution in Mts Al-Wardah Tembung where this research provides several questions to find out how an educational institution does a curriculum development based on Islamic values in the management of educational institutions such as 1). How is the evaluation carried out on the effectiveness of the curriculum based on Islamic values in improving the quality of education, 2). How the impact of the curriculum based on Islamic values on improving the morals and character of students, 3). Challenges faced in the implementation of curriculum based on Islamic values in educational institutions 4). How to compare the results of following a curriculum based on Islamic values with a conventional curriculum in educational institutions. The research method used in this research is descriptive qualitative research using observation techniques and also interviews with the head of the Mts Al- Wardah Tembung school madrasah. And the results of this research can be concluded that it feels like a curriculum development based on Islamic values in the management of Islamic educational institutions at the Mts Al-Wardah school that an implementation of the curriculum in this educational institution has had a positive impact in increasing awareness of religious values, morals and character of students.